APLIKASI MULTIVARIATE MULTIPLE REGRESSION UNTUK MENDUGA FAKTOR-FAKTOR YANG MEMENGARUHI KESEJAHTERAAN MASYARAKAT - SWASTINI, PUTU EKA; SUKARSA, I KOMANG GDE; N. KENCANA, I PUTU EKA (E-Jurnal Matematika; Vol 3 No 3 (2014)DO - 10.24843/MTK.2014.v03.i03.p071, 2014)
This essay aimed to apply the Multivariate Multiple Regression (MMR) methodfor the welfare issue. The predictor variables in the model are 18 indicators of welfare according to Indonesian Central Bureau of Statistic (BPS) and  the response variables are Human Development Index (IPM), Gross Regional Domestic Product (PDRB), and Regional Crime Index (IKD). In modeling the relationship between q responses and a single set of predictor variables , MMR assumed each pairs of two response variables were correlated and its distribution follows normal multivariate. Based on the result of MMR, we obtained six out of 18 predictor variables simultaneously affect IPM and  PDRB. The final model showed the association between those variables very closed to 100 percent .
Keywords: GLM, multivariate, regression, welfare